Effectiveness of an oral health care training workshop for school teachers: a pilot study (2013)
Background: School teachers play key roles in imparting appropriate and up-to-date knowledge to pupils and students. However, most teachers in developing countries like Nigeria have poor knowledge and motivation about oral health which may be due to inadequate training in the area of oral health. This might be one of the reasons for the poor oral hygiene among them and their students. Objectives: To evaluate the effectiveness of an oral health care training programme organized for teachers in Eruwa, Oyo state, Nigeria. Methods: An intervention study was conducted among 40 school teachers who attended a two day oral health training workshop at Eruwa, headquarters of Ibarapa East Local Government Area. Training methods included lectures and demonstrations on aetiology, clinical features, treatment and prevention of common oral diseases. Pre- and post- evaluation written tests were administered to the participants to assess the effectiveness of the training. The knowledge scores were rated as poor, fair and good knowledge scoring <50.0%, 50.0-60.0% and > 60.0% respectively. Frequencies, percentages and means of relevant variables were generated. Paired t-test was used to compare means at P<0.05. Result: The mean age of the teachers was 40.13 ±7.24 years. There were 16 (40.0%) males and 24 (60.0%) females. Twenty (50.0%) of the participants had poor pre-training knowledge as compared to 7 (17.5%) after the training. Thirteen (32.5%) had fair pre-training knowledge as compared to 17 (42.5%) post training. Only (2.5%) of the participants had good pre-training knowledge as compared to 18 (45.0%) post training. The mean scores of the pre- and post-evaluation tests were 31.70 ±11.31 and 48.20 ±11.16 respectively. There was a statistically significant difference between the mean scores of the pre and post evaluations P<0.05. Conclusions: The training workshop improved the knowledge ofschool teachers regarding oral health